Lixisenatide: A New Member of the Glucagon-Like Peptide 1 Receptor Agonist Class of Incretin Therapies - Shaefer, Charles F. (Clin Diabetes, 2016)
In Brief In the past decade, various incretin-based therapies have emerged in clinical practice. These drugs, including dipeptidyl peptidase-4 inhibitors and glucagon-like peptide 1 (GLP-1) receptor agonists lower A1C with weight-neutral or weight-lowering effects and a relatively lower risk of hypoglycemia. This article provides a review of lixisenatide, a once-daily GLP-1 receptor agonist for the treatment of type 2 diabetes.